BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI PRIA SEBAGAI PESERTA KB DI KELURAHAN TEMBILAHAN KOTA TAHUN 2008 - Desmalita Desmalita; Dien GA Nursal; Suryati Suryati (Faculty of Public Health, Andalas University, 2009)
Male participation is actual form of caring and responsibility of male/husband in execution of family planning program and reproduction health. In Indonesia, male participation was only 1,3%, covered condom 0,9 % and vasectomy 0.4'%. While target in Mid-Term Development Planning is 4,5% in the year 20/0. In Sub-district Tembilahan Kola, attainment of male KB is only 4S people ( 1,34%) and 3569 KB participants. This research was aimed to know factor related to male participation asfamily planningprogram participant in Sub District Tembilahan Kola work region of District TembilahanPublic Health Center Sub Province Indragiri Hilir Riatt 200S. Research design was cross sectional, done at two population of male becoming KB participant (31 sample) and population of male which is not become KB participant (31 sample). The research was done by questionnaire, by interviewing the responders. The univariat and bivariat analyses was done using SPSS 1 4. Result of research found that there was significant relationship between education, level of knowledge, and the role of wife. While there was no significant relationship between services reachability of KB with maleparticipation as participant in family planning program in sub district Tembilahan Kota.lt is necessary to give informationAnd education is required in the effort of improving male participation as KB participant, spreadingof information and motivation matching with characteristic level of education. Increases equipment supply offacilities and basic facilities of KB and the extension of service reachability of male contraception in sub-district Tembilahan Kola.